Preliminary observations of the reproductive biology and diet for the Norwegian skate Dipturus nidarosiensis (Rajidae) from the Central Western Mediterranean Sea ... - Follesa, Maria C.; Cannas, Rita; Cabiddu, Serenella; Cau, Alessandro; Mulas, Antonello; Porcu, Cristina; Cau, Angelo (Cybium, 2012)
Twenty-three Dipturus nidarosiensis (Collett, 1880) (Elasmobranchii: Rajidae) were collected off the coasts of Sardinia between 550 m and 1688 m of depth in 2005-2011. A first description of some biological aspects as the vertical distribution, the reproduction and the diet of the Norwegian skate from the Central Western Mediterranean is provided. Females attained a greater length than males, they mature at larger sizes and were found mature always at depths of 550-600 m in the same area of the Southern coast of Sardinia. The diet of D. nidarosiensis was based almost entirely on decapod crustaceans and completed by bony fish. ...